Thalidomide monotherapy or in combination with dexamethasone in patients with refractory multiple myeloma - Hellmann, Andrzej; Dietrich, Grażyna; Ciepłuch, Hanna; Knopińska-Posłuszny, Wanda; Prejzner, Witold; Baran, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2001)
32 patients with refractory multiple myeloma (9 out of the patients relapsed after high-dose chemotherapy and autologous peripheral blood stem cell transplantation and 1 patient after allogeneic bone marrow transplantation) were treated with thalidomide. Approval of the Independent Bioethics Committee for Scientific Research was obtained. Written informed consent was obtained from patients before entry to the study. Before entry to the study every patient had neurological examination. During the treatment, physical and neurological examination, as well as blood chemistries and bone marrow biopsy were performed every 4 weeks. Thalidomide was administrated for a median of 14,5 weeks (range 2 to 60 weeks). The starting dose was 200 mg a day during the first week and the dose was increased to 400 mg a day in fourth week. Twelve patients were treated parallelly with dexamethasone at the dose of 40 mg a day for 4 days a month. Good response, defined as decrease in monoclonal protein more than 20% in comparison to the monoclonal protein level at the beginning of the treatment, was observed in 16 (50%) patients. Two of them achieved complete remission with elimination of monoclonal protein, normalization of bone marrow and peripheral blood. The treatment was most effective in 14 (87,5%) of 16 patients between 4 and 12 weeks of drug administration. White blood cells and platelets count increase was preceeded by their decrease between 4 and 12 weeks of thalidomide treatment. Of the 12 patients who were treated with dexamethasone and thalidomide, seven (58%) achieved regression of the disease. Reduction in the level of monoclonal protein was associated with reduction in the percentage of plasma cells in bone marrow and β-2 microglobuline. Most patients suffered from adverse events (vertigo, constipation, peripheral polyneuropathy, somnolence and a tendency to pancytopenia). 8 patients (6 with good response) discontinued treatment due to adverse events. 5 patients died of multiple myeloma progression. Thalidomide may be an effective treatment for patients with relapsed after high-dose chemotherapy and refractory myeloma. It seems useful to combine dexamethasone with thalidomide, what can overcome resistance to chemotherapy.